Treatment decision-making capacity in non-consensual psychiatric treatment: a multicentre study. (9th March 2017) - Mandarelli, G.; Carabellese, F.; Parmigiani, G.; Bernardini, F.; Pauselli, L.; Quartesan, R.; Catanesi, R.; Ferracuti, S.
Abstract : Aims: To evaluate treatment decision-making capacity (DMC) to consent to psychiatric treatment in involuntarily committed patients and to further investigate possible associations with clinical and socio-demographic characteristics of patients. Methods: 131 involuntarily hospitalised patients were recruited in three university hospitals. Mental capacity to consent to treatment was measured with the MacArthur Competence Assessment Tool for Treatment (MacCAT-T); psychiatric symptoms severity (Brief Psychiatric Rating Scale, BPRS-E) and cognitive functioning (Mini Mental State Examination, MMSE) were also assessed. Results: Mental capacity ratings for the 131 involuntarily hospitalised patients showed that patients affected by bipolar disorders (BD) scored generally better than those affected by schizophrenia spectrum disorders (SSD) in MacCAT-T appreciation ( p < 0.05) and reasoning ( p < 0.01). Positive symptoms were associated with poorer capacity to appreciate ( r = −0.24; p < 0.01) and reason ( r = −0.27; p < 0.01) about one's own treatment. Negative symptoms were associated with poorer understanding of treatment ( r = −0.23; p < 0.01). Poorer cognitive functioning, as measured by MMSE, negatively affected MacCAT-T understanding in patients affected by SSD, but not in those affected by BD (SSD r = 0.37; p < 0.01; BD r = −0.01; p = 0.9). Poorer MacCAT-T reasoning was associated with more manic symptoms in the BD group of patients but not in the SSD group (BD r = −0.32; p < 0.05; SSD r = 0.03; p = 0.8). Twenty-two per cent ( n = 29) of the 131 recruited patients showed high treatment DMC as defined by having scored higher than 75% of understanding, appreciating and reasoning MacCAT-T subscales maximum sores and 2 at expressing a choice . The remaining involuntarily hospitalised patients where considered to have low treatment DMC. Chi-squared disclosed that 32% of BD patients had high treatment DMC compared with 9% of SSD patients ( p < 0.001). Conclusions: Treatment DMC can be routinely assessed in non-consensual psychiatric settings by the MacCAT-T, as is the case of other clinical variables. Such approach can lead to the identification of patients with high treatment DMC, thus drawing attention to possible dichotomy between legal and clinical status.